Relationship between the diameters of sphenopalatine foramen and alveolar antral artery and maxillary sinus volume: a retrospective cone beam computed tomography study - Arif Turkoglu; Halil Ayyildiz (BMC Oral Health)
Abstract Background It has been reported that the morphology and volume of the maxillary sinus (MS), which is the largest paranasal sinus, have an impact on the success of surgical procedures that are to be performed in the MS region. The aim of this study was to evaluate the effect of sphenopalatine foramen (SPF) and alveolar antral arterial canal (AAAC) diameters and posterior dentition status (PDS) on maxillary sinus volume (MSV). Methods The study included cone beam computed tomography (CBCT) images of patients over 20 years of age with no impacted teeth in the MS, and in whom the entire MS margins, AAAC, and SPF were clearly visible. Only images without metal or motion artefacts and with adequate clarity were selected. In this study, a total of 90 patients’ CBCT images, 47 males and 43 females, with a mean age of 47.10 years, were evaluated. AAAC diameter was measured on the coronal section, and SPF diameter was measured on the axial section of CBCT. MSV was measured on axial sections with 3D DOCTOR software. Results The mean MSV was 14.02 cm3, 14.47 cm3 in dentate patients, and 13.21 cm3 in edentulous patients. The mean MSV was found to be 24.99 cm3 in the female group and 30.84 cm3 in the male group. Statistical analysis revealed that the mean MSV and AAAC diameter were higher in males (p = 0.000). While the mean MSV was higher in the dentate group, this disparity did not demonstrate statistical significance (p = 0.126). A weak negative correlation was identified between MSV and SPF diameter (p = 0.004, r= -214). Conclusions In the present study, CBCT evaluation revealed that a negative correlation was found between MSV and SPF, and a positive correlation between SPF and AAAC, while no significant relationship was observed between MSV and AAAC. It is recommended that the sample size be increased in future studies to evaluate the possible statistical relationship between MSV and AAAC. The AAAC diameter was larger in patients with edentulous PDS, suggesting increased caution is needed during sinus elevation in such cases. MSV was higher in males, indicating its potential use in sex determination in forensic sciences.